Strategi Ekspansi BYD pada Pasar Indonesia Melalui Instrumen Foreign Direct Investment (FDI) Tahun 2023-2025 - Putra Bakri, Rayhan Rafie; Kresnawati, Megahnanda Alidyan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This article analyzes how BYD's expansion strategy in the Indonesian market is optimized through the use of Foreign Direct Investment (FDI) instruments during the 2023–2025 period. This research adopts a qualitative method. The growing competition in Indonesia’s Electric Vehicle (EV) market is driven by several factors, such as the absence of vehicle exhaust emissions, government incentives in the form of tax reductions for electric vehicles, exemption from odd-even traffic restrictions, and various other conveniences. As a leading electric vehicle manufacturer from China, BYD also aims to take part in the growing EV market in Indonesia. However, in the process, BYD faces challenges in entering the rapidly developing Indonesian EV sector. This study applies a qualitative method using a case study approach, examining foreign investment policies, government regulations, and the economic and infrastructure factors that support BYD’s successful investment in Indonesia. The findings indicate that the optimization of FDI through fiscal incentives, strategic partnerships with local companies, and the strengthening of domestic supply chains are key factors supporting BYD’s expansion. In addition, increasingly favorable regulations, such as tax incentive policies and the development of the EV ecosystem, also play a role in enhancing investment attractiveness. However, challenges such as bureaucratic hurdles, infrastructure readiness, and competition with other brands remain obstacles to be addressed. With the right strategy, BYD can leverage FDI as a key instrument to accelerate its expansion in Indonesia and solidify its position as a major player in the global electric vehicle industry.